Et Dieu-- créa la femme = " ... and God created woman" [videorecording (DVD)] - Lévy, Raoul, 1922-1966; Vadim, Roger; Bardot, Brigitte; Jürgens, Curd, 1915-1982; Trintignant, Jean-Louis; Marken, Jane, 1895-1976; Tissier, Jean, 1896-1973; Corey, Isabel, 1939-2011; Ventura, Jacqueline, 1920-; Ciron, Jacques; Faivre, Paul, 1886-1973; Mourey, Jany; et al. (Criterion collection, 2000)
Juliette is an 18 year-old orphan whose unbridled appetite for pleasure shakes up all of St. Tropez. Her sweet but naïve husband Michel endures beatings, insults and mambo in his attempts to tame her wild ways.